The Development of a Cloud Based Training Model with Case-Based Learning To Enhance Media Literacy of Public Relation Officers in Non-Profit Organization - Yeamprayunsawasd, Napin; Tantrarungroj, Pornsook (An Online Journal of Education, 2021)
The purpose of this research study was to design and develop a Cloud-based training model with case-based learning to enhance the media literacy of public relations officers in non-profit organizations. This was a preliminary research study conducted with experts using results to develop a model, and the sample consisted of seven experts and five advisors. The research instruments were expert interviews and model evaluation forms. The result of the study concluded that the model consisted of five elements, namely: 1) Training objectives; 2) Participants and trainers; 3) Information and communication technology on the Cloud; 4) Case-based learning process; and 5) Evaluation. The training activities can be divided into the three phases, as follows: Phase 1: Pre-training, including 1.1) Orientation of trainees, and 1.2) Measurement of media literacy before training. Phase 2: Training, including 2.1) Instructor presents a case study; 2.2) Trainees examine the case study; 2.3) Trainees discuss questions to seek answers; 2.4) Instructor and trainees discuss problems to find common answers; and 2.5) Instructor assigns trainees work. Phase 3: Training follow-up, including 3.1) Summarize and evaluate the trainees’ learning outcomes; and 3.2) Measure media literacy after training. The result of the evaluation revealed the highest level (M = 4.65, SD = 0.49).